DEVELOPMENT OF A RAINWATER ELECTROLYSIS PRACTICUM TOOL TO ENHANCE STUDENT ENGAGEMENT IN ELECTROCHEMISTRY LEARNING - Lestari, Nimas Ayu; Prima, Eka Cahya; Riandi, Riandi; Widodo, Ari (Universitas Pakuan, 2025)
Electrolysis is a fundamental concept in electrochemistry, yet its real-world applications are often overlooked in classroom settings. This study aims to design and develop a rainwater electrolysis practicum tool that contextualizes electrochemical concepts, enabling students to directly observe chemical processes related to environmental issues such as acid rain. An experimental method was conducted by varying the applied potential difference (4, 6, 8, and 10 V) and measuring pH changes in rainwater. The apparatus was designed and fabricated by the authors, adapting established electrolysis principles into a hands-on practicum tool. The results indicate that increasing potential difference influences localized pH shifts, where the cathode environment becomes more basic while the anode becomes more acidic, visualizing ion distribution during electrolysis. Student responses, collected through questionnaires, revealed high levels of motivation, ease of use, attractiveness, and perceived usefulness of the practicum product. These findings demonstrate the effectiveness of the practicum in enhancing students' engagement and understanding of electrochemistry concepts. In conclusion, the rainwater electrolysis practicum developed in this study bridges the gap between theoretical knowledge and practical applications, fostering a contextualized learning experience that aligns with the objectives of science education while also embedding environmental relevance.